2021
DOI: 10.1002/chem.202103043
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Mn2+ Doped 1D Hybrid Lead Halide Perovskite with Highly Efficient, Tunable and Stable Broadband Light Emissions

Abstract: Mn2+ doped colloidal three‐dimensional (3D) lead halide perovskite nanocrystal (PNC) has attracted intensive research attention; however, the low exciton binding energy and fatal optical instability of 3D PNC seriously hinder the optoelectronic application. Therefore, it remains significant to explore new stable host perovskite with strongly bound exciton to realize more desirable luminescent property. In this work, we utilized bulk one‐dimensional (1D) hybrid perovskite of [AEP]PbBr5 ⋅ H2O (AEP=N‐aminoethylpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…Xia utilized trap management of CsCdCl 3 :Mn 2+ :Zr 4+ crystals to realize X-ray phosphor for 3D imaging . It has been shown that it is feasible to use Sb 3+ and Mn 2+ as dopants to improve the photophysical properties of the host materials. , Therefore, we choose the compounds containing Cd element as the host material to develop a new afterglow crystal material by codoping Sb 3+ and Mn 2+ …”
Section: Introductionmentioning
confidence: 99%
“…Xia utilized trap management of CsCdCl 3 :Mn 2+ :Zr 4+ crystals to realize X-ray phosphor for 3D imaging . It has been shown that it is feasible to use Sb 3+ and Mn 2+ as dopants to improve the photophysical properties of the host materials. , Therefore, we choose the compounds containing Cd element as the host material to develop a new afterglow crystal material by codoping Sb 3+ and Mn 2+ …”
Section: Introductionmentioning
confidence: 99%
“…Organic–inorganic hybrid metal halide (OIHMH) materials have been drawing tremendous attention due to their outstanding optical properties and gained considerable interests in the field of photoelectric devices such as photodetectors, solar cells, and light-emitting diodes (LEDs). Moreover, compared to all-inorganic halide perovskites, the inorganic units were enabled with the structural confinement effect by the large organic balance cations to generate low-dimensional structures. The one-dimensional (1D) perovskite structure means that the metal halide octahedrons are connected in a chain. Compared with high-dimensional materials, 1D materials can make exciton self-trap more easily at any phonon–exciton interaction strength, resulting in distinct optical properties such as large Stokes shift.…”
Section: Introductionmentioning
confidence: 99%
“…21 Likewise, Jing et al created [AEP]Pb 1− x Mn x Br 5 ·H 2 O through a cooling crystallization process and printed it on commercial paper using screen printing, which exhibited orange-red luminescence under UV-light excitation. 22 Unfortunately, anti-counterfeiting markings created with single fluorescence emission can be easily duplicated and counterfeited. Therefore, HPs with multicolor and multimodal fluorescence are one of the most promising candidates for high-security-level anti-counterfeiting applications.…”
Section: Introductionmentioning
confidence: 99%